Rancang bangun aplikasi pembayaran spp berbasis web - Denih Denih; Raditya Galih Wendasmoro; Samuel Ramos (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
SMK Tri Patria Nusantara is one of the educational institutions whose payment system has not yet been computerized, the input is still recorded in the book as data processing for students who have paid tuition fees. And the data storage is still in archiving in the ledger, so that the administrative staff must record the names of students who have paid administratively one by one which can result in misinformation regarding data collection on the names of students who have paid and make it difficult for administrative staff to find or provide data that is needed. If necessary, then a web-based tuition payment system is needed. The stages of system development in making this information system use the Prototyping model method which consists of the planning stage, the analysis stage, the design stage, and the implementation stage. Using the PHP programming language in its manufacture and MySQL Server as the database. The results of the research are that the system that was running previously did not have a SPP payment data storage in the form of a database, which is still in the form of a bookkeeping so that the data storage process becomes more difficult to search, so it is proposed to design and manufacture a web-based SPP payment information system at SMK Tri Patria Nusantara. With the existence of a web-based tuition payment information system, it is hoped that it will make it easier for Administatative staff to process computerized student administration payment data.